Mortality and causes of death among Croatian male Olympic medalists - Radonic, V.; Kozmar, D.; Pocanic, D.; Jerkic, H.; Bohacek, I.; Letilovic, T. (Croatian Medical Journal, 2017)
To compare the overall and disease-specific mortality of Croatian male athletes who won one or more Olympic medals representing Yugoslavia from 1948 to 1988 or Croatia from 1992 to 2016, and the general Croatian male population standardized by age and time period. Methods: All 233 Croatian male Olympic medalists were included in the study. Information on life duration and cause of death for the Olympic medalists who died before January 1, 2017, was acquired from their families and acquaintances. We asked the families and acquaintances to present medical documentation for the deceased. Data about the overall and disease-specific mortality of the Croatian male population standardized by age and time period were obtained from the Croatian Bureau of Statistics (CBS). Overall and disease-specific standard mortality ratios (SMR) with 95% confidence intervals (CI) were calculated to compare the mortality rates of athletes and general population. Results: Among 233 Olympic medalists, 57 died before the study endpoint. The main causes of death were cardiovascular diseases (33.3%), neoplasms (26.3%), and external causes (17.6%). The overall mortality of the Olympic medalists was significantly lower than that of general population (SMR 0.73, 95% CI 0.56-0.94, P = 0.013). Regarding specific causes of death, athletes` mortality from cardiovascular diseases was significantly reduced (SMR 0.61, 95% CI 0.38-0.93, P = 0.021). Conclusions: Croatian male Olympic medalists benefit from lower overall and cardiovascular mortality rates in comparison to the general Croatian male population.